Examining if being overweight really confers protection against dementia: Sixty-four year follow-up of participants in the Glasgow University alumni cohort study. Issue 1 (December 2016) - Batty, G.; Galobardes, Bruna; Starr, John; Jeffreys, Mona; Davey Smith, George; Russ, Tom
Abstract Background Recent large-scale studies suggest that obesity and overweight may conferprotection against future dementia. This observation could, however, be generated by reverse causality. That is, weight loss in the incipient phase of dementia ascribed to diminished self-care, including sub-optimal nutrition, would have the effect of generating such an inverse association. One approach to circumventing this problem would be to measure weight in a population which is young enough to be free of the symptoms of dementia which is then followed up for dementia occurrence over many decades. Methods In a prospective cohort study, body mass index, and other potential risk factors, were measured in 9547 male university undergraduates (mean age 20.5 years) in 1948–68 who were then linked to national mortality registers. Results Of 2537 deaths over a mean of 50.6 years follow up, 140 were ascribed to dementia. There was no association between overweight and future dementia deaths (age-adjusted hazard ratio; 95 % confidence interval: 0.93; 0.49, 1.79). Conclusion In this cohort study of former university students, being overweight in youth did not confer protection against later dementia death.